Electrical characteristics of dendrites and dendritic spines in intracellularly stained CA3 and dentate hippocampal neurons - Turner, DA (J Neurosci, 1983)
Theoretical parameters of synaptic efficacy were studied in a detailed cable model of in vitro hippocampal neurons. CA3 pyramidal cells (n = 9) and dentate granule neurons (n = 6) were injected with horseradish peroxidase (HRP) after brief physiological analysis. The dendrites of these HRP-stained neurons were measured and approximated by a series of cylindrical segments. Specific electrical values of the neurons were calculated on a steady-state basis, using a cable analysis of the dendritic segments. The evaluation was expanded to include idealized dendritic spines. Average spine dimensions were determined by electron microscopic measurements. The density distribution of spines was patterned after reported Golgi measurements of similar neurons. The average electrotonic length of the CA3 apical dendrites was determined to be 0.69 length constant. These CA3 neurons were not well approximated by a single equivalent cylinder coupled to a soma (E-C model). The dentate granule cells exhibited an average electrotonic length of 1.12 length constants and could be adequately represented by the E-C model. Synaptic efficacy was estimated by the transfer of either charge or steady-state voltage from a spine input to the soma. Charge transfer varied as a function of the electrotonic distance from the soma to the input site. Voltage transfer, however, did not vary as a simple function of electrotonic distance. Voltage and charge transfer averaged less than 10% loss across the dendritic spine neck. These calculations, based on specific neuronal anatomy, predict that dendritic spines do not significantly attenuate steady-state electrical signals.